Inventory on the dietary assessment tools available and needed in africa: a prerequisite for setting up a common methodological research infrastructure for nutritional surveillance, research, and prevention of diet-related non-communicable diseases. Issue 1 (2nd January 2018) - Pisa, Pedro T.; Landais, Edwige; Margetts, Barrie; Vorster, Hester H.; Friedenreich, Christine M.; Huybrechts, Inge; Martin-prevel, Yves; Branca, Francesco; Lee, Warren T. K.; Leclercq, Catherine; Jerling, Johann; Zotor, Francis; et al.
Abstract: Objective: To carry out an inventory on the availability, challenges, and needs of dietary assessment (DA) methods in Africa as a pre-requisite to provide evidence, and set directions (strategies) for implementing common dietary methods and support web-research infrastructure across countries. Methods: The inventory was performed within the framework of the "Africa's Study on Physical Activity and Dietary Assessment Methods" (AS-PADAM) project. It involves international institutional and African networks. An inventory questionnaire was developed and disseminated through the networks. Eighteen countries responded to the dietary inventory questionnaire. Results: Various DA tools were reported in Africa; 24-Hour Dietary Recall and Food Frequency Questionnaire were the most commonly used tools. Few tools were validated and tested for reliability. Face-to-face interview was the common method of administration. No computerized software or other new (web) technologies were reported. No tools were standardized across countries. Conclusions: The lack of comparable DA methods across represented countries is a major obstacle to implement comprehensive and joint nutrition-related programmes for surveillance, programme evaluation, research, and prevention. There is a need to develop new or adapt existing DA methods across countries by employing related research infrastructure that has been validated and standardized in other settings, with the view to standardizing methods for wider use.